Evaluating the psychometric properties of the eHealth Literacy Scale in Brazilian adults - Fábio Luiz Mialhe; Katarinne Lima Moraes; Helena Alves de Carvalho Sampaio; Virgínia Visconde Brasil; Vanessa da Silva Carvalho Vila; Gustavo Hermes Soares; Flávio Rebustini
ABSTRACT Objective: To translate and adapt the eHealth Literacy Scale for the cultural reality of Brazil and to evaluate the psychometric properties of its Brazilian Portuguese version. Methods: The instrument was translated and adapted to Brazilian Portuguese and applied to a sample of 502 individuals from 18 to 80 years old who lived in the surrounding areas of six Family Health Units of a city in the countryside of the state of São Paulo, Brazil. The data was evaluated using exploratory and confirmatory factor analysis, item response theory, and instrument reliability measures (Cronbach's alpha and McDonald's omega). Results: The eHealth Literacy Scale - Brazilian version (eHEALS-Br) presented an excellent internal consistency (α = 0.95 e ω = 0.95), with only one dimension and an explained variation of 81.79%. Conclusions: The Brazilian version of the instrument showed excellent psychometric properties to measure the levels of digital health literacy in adults from the country.